2022
DOI: 10.13057/biodiv/d230248
|View full text |Cite
|
Sign up to set email alerts
|

Screening of endophytic fungi as potential antagonistic agents of Pyricularia oryzae and evaluation of their ability in producing hydrolytic enzymes

Abstract: Abstract. Putri ND, Sulistyowati L, Aini LQ, Muhibuddin A, Trianti I. 2022. Screening of endophytic fungi as potential antagonistic agents of Pyricularia oryzae and evaluation of their ability in producing hydrolytic enzymes. Biodiversitas 23: 1048-1057. One of the most important phytopathogenic fungi is Pyricularia oryzae, as it is the causative agent of rice blast diseases, which is the most destructive and detrimental disease in rice. Biological control using endophytic fungi can be an alternative to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…Previous studies indicating that chitinases are involved in triggering a plant's defense mechanisms corroborate the current results (Baek et al, 1999;Gueye et al, 2020). The current results are also supported by studies that have found that the hydrolytic enzymes (cellulase, chitinase, protease, and b-(1,3)-glucanases) produced by T. asperellum, T. harzianum, and T. longibrachiatum have a high level of antagonistic activity against F. oxysporum (Schirmböck et al, 1994;Putri et al, 2022). These enzymes play a key role in the breakdown of the pathogen's cell walls, which facilitates simple invasion and colonization by the biocontrol agents, induces a defense response and slows the spread of the pathogen while also indirectly promoting plant growth and development (Qualhato et al, 2013;Cherkupally et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies indicating that chitinases are involved in triggering a plant's defense mechanisms corroborate the current results (Baek et al, 1999;Gueye et al, 2020). The current results are also supported by studies that have found that the hydrolytic enzymes (cellulase, chitinase, protease, and b-(1,3)-glucanases) produced by T. asperellum, T. harzianum, and T. longibrachiatum have a high level of antagonistic activity against F. oxysporum (Schirmböck et al, 1994;Putri et al, 2022). These enzymes play a key role in the breakdown of the pathogen's cell walls, which facilitates simple invasion and colonization by the biocontrol agents, induces a defense response and slows the spread of the pathogen while also indirectly promoting plant growth and development (Qualhato et al, 2013;Cherkupally et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…To induce enzyme production, basal salts of the following compositions were added: MgSO 4 .7H 2 O (0.3 g), (NH 4 ) 2 SO 4 (3 g), KH 2 PO 4 (2 g), agar (15 g). They were augmented with 1% (w/v) colloidal chitin (Rojas-Avelizapa et al, 1999;El-Sobky et al, 2019), 1% (w/v) CMC, 1% (w/v) gelatin, and 2.0% (w/v) laminarin), to detect the enzymes chitinase, cellulase, protease and b-(1-3) glucanase (Nagpure et al, 2014;Putri et al, 2022), respectively. The incubation was continued for 24 h, and the culture filtrate separated by filtration and centrifugation (at 5000 rpm, 4°C, for 10 min) and used as the enzyme source (Maria et al, 2005;Agrawal and Kotasthane, 2012;Saravanakumar et al, 2017).…”
Section: Biocontrol-related Enzymesmentioning
confidence: 99%
“…6). Chitinase plays a key role in hyphal/mycelium development and branching, spore production and germination, fungal cell wall degradation or morphogenesis of fungal cell wall structure [46]. This key role defines the role of B. cereus SAHA 12.13 chitinase enzyme in inhibiting pathogenic fungi, namely inhibiting spore production and germination.…”
Section: Antagonistic Activity Of B Cereus Saha 1213 Isolates Against...mentioning
confidence: 99%
“…The PCR cycles included 3 minutes of pre-denaturation at 95°C, 30 seconds of denaturation at 95°C, 30 seconds of annealing at 50°C, 1 minute of extension at 72°C, 1 minute of final extension at 72°C. PCR products were analyzed by electrophoresis in 1% agarose gel and treated with 0.75 l DNA dye (Nandika et al 2021;Putri et al 2022). DNA double helix sequences were assembled and analyzed using Genetyx (version 11.0) and Genetyx-ATSQ (version 4.0) software (Genetyx, Tokyo, Japan) sequentially and compared with same DNA sequences accessed from DDBJ/ EMBL/ GenBank via NCBI BLAST program (Parwanayoni 2018).…”
Section: Molecular Identificationmentioning
confidence: 99%